Scalpel versus diathermy skin incision in elective surgery: a comparative study - Joty, Syeda Mehbuba; Saiyara, Noshin; Khan, Mahidur Rahman; Tareq Anwar Shishir, M.; Akhter, Mahbuba; Islam, Faridul; Sultana, Nishat (International Journal of Research in Medical Sciences, 2024)
Background: Elective surgeries often employ either diathermy or scalpel for skin incisions, yet there is limited comprehensive research comparing the two methods. This observational study aims to compare the clinical and medical outcomes of diathermy and scalpel skin incisions in elective surgeries. Methods: This retrospective observational study was conducted at the Enam Medical College, Dhaka, Bangladesh, over a period of 1.5 years. A total of 150 patients were included, with 75 in Group A (Scalpel Incision) and 75 in Group B (Diathermy). Various outcomes such as comorbidities, incision time, blood loss, post-operative complications, pain scores and wound grading using Surgical Site Infection (SSI) Grading were assessed. Results: The study found that diathermy incisions were associated with shorter incision times (mean: 24.81 seconds) and reduced blood loss (mean: 1.82 ml) compared to scalpel incisions (mean incision time: 53.14 seconds, mean blood loss: 9.61 ml). Post-operative complications varied, with hematoma being more prevalent in the scalpel group (20.00%). Pain scores were consistently lower in the diathermy group across multiple post-operative days. Most participants in both groups had no SSI according to the employed SSI Grading. Conclusions: The study suggests that diathermy may be a viable alternative to scalpel incisions in elective surgeries, offering benefits such as reduced incision time and blood loss. However, the choice between the two should be individualized based on patient characteristics and surgical requirements. Further research is needed to confirm these findings and provide more targeted recommendations.